2017
DOI: 10.18203/2349-2902.isj20172763
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of laparoscopic versus open appendectomy: a comparative study

Abstract: Background: The advantages of laparoscopic appendicectomy over open appendicectomy were questioned because the recovery period with open appendicectomy was brief. In this study, the two techniques were compared with respect to post-operative pain and duration of us of an analgesic, complications such as vomiting, ileus, intra-abdominal abscess, wound infection, length of post-operative stay, and return to routine work.Methods: 50 patients who met the inclusion criteria were included in the study was subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…In LA group mean analgesic dose required was 2.45 ± 0.71 and in OA group analgesic dose required was 4.40 ± 0.93. Similar results were obtained by [2,11,12] they showed number of analgesic dose requirement was less in LA group than OA group, frequency of use of analgesia was less in laparoscopic appendectomy as compared to open appendectomy. Small trocar incisions of laparoscopy also leads to minimum trauma to abdominal wall, less pain and faster recovery.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In LA group mean analgesic dose required was 2.45 ± 0.71 and in OA group analgesic dose required was 4.40 ± 0.93. Similar results were obtained by [2,11,12] they showed number of analgesic dose requirement was less in LA group than OA group, frequency of use of analgesia was less in laparoscopic appendectomy as compared to open appendectomy. Small trocar incisions of laparoscopy also leads to minimum trauma to abdominal wall, less pain and faster recovery.…”
Section: Discussionsupporting
confidence: 83%
“…This could be because the minimally invasive operation (LA) by definition allow for a quicker recovery as compared to open surgery. Similar results were also obtained by [13,14,11] reported length of hospital stay was shortened by 1.1 day in laparoscopic approach and duration of hospital stay was significantly low for laparoscopic group (2.84±0.9) as compared to open group (7.68±2.38). It has been shown that shorter hospital stay in LA group as compared to OA group was attributed to minimal trauma to abdominal wall which is a significant factor in postsurgical discomfort and lead to better mobility and earlier ambulation.…”
Section: Length Of Hospital Staysupporting
confidence: 85%
“…For many treatments, including cholecystectomy, laparoscopic surgery has lately acquired widespread acceptability because it provides advantages like reduced scarring, less pain, and an earlier return to normal activities 18 . The first LA was carried out by German gynaecologist Semm in 1981 19 . In 1982, he discussed the procedure at a surgery conference.…”
Section: Discussionmentioning
confidence: 99%
“…However B. A. Kolhar [20] showed the age of patients ranged from 13 years (youngest) to 53 years (oldest) with a mean age of 25.08 years in open and 23.36 years in laproscopic group.…”
Section: Ao: Open Appendicectomy Group La: Laparoscopic Appendicectom...mentioning
confidence: 99%